Answer:
Step-by-step explanation:
mean
I think.
Answer:
see below
Step-by-step explanation:
The exponent rules that apply are ...
(a^b)(a^c) = a^(b+c)
a^-b = (1/a)^b
(a^b)^c = a^(b·c)
_____
These let you rewrite the given function as ...
f(x) = (3^(2x))(3^1) = 3(3^(2x)) = 3(3^2)^x = 3·9^x
and
f(x) = 3^(2x+1) = (3^-1)^(-(2x+1)) = (1/3)^-(2x+1)
Answer:
4 in 4in 6 in = 96 in
Step-by-step explanation:
Answer:
-6
Step-by-step explanation:
it's asking when x is equal to -5 what is y equal to?
there's only one point when x=-5 and it's -6
so the point is (-5,-6) and y is equal to -6
hope this helps and makes sense <3
do well babe
The answer is C because -2 is less than or equal to 5. (4 times 0 is 0)